2014
DOI: 10.4315/0362-028x.jfp-13-284
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Strategies for Deoxynivalenol and Zearalenone Reduction in Stored Adlay (Coix lachryma-jobi L.) Grains

Abstract: Improperly practiced postharvest procedures can pose mycotoxin-related risks in the production of medicinal herbs. As a health food with pharmacological supplements, cereal-based adlay has been broadly used in oriental medical practice. Compared with the standard production protocol, three provisional critical control points (CCPs) in the conventional procedure were identified and assessed for mycotoxin contamination in the adlay from small farms in Korea. Although various mycotoxins were present, the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Therefore, in our model, we used 100–1,000 ng/ml DON, which corresponds to in vivo exposure levels (about 0.1–1.0 mg DON/kg food/feed), which is assumed to be realistic within the average contamination level in both food and feed. According to our previous investigation, although the DON contamination levels in total adlay were 0.37–2.55 mg/kg, the bran levels were around 0.4–1.0 mg/kg adlay ( 5 ). Although high levels of trichothecene mycotoxins such as nivalenol and DON (>2,000 ng/ml) significantly influence enterocyte viability through activation of pro-apoptotic processes, ingestion of the realistic milder levels of DON (<1,000 ng/ml) retarded the epithelial cell migration (restitution), representing the initial step in the wound healing process in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, in our model, we used 100–1,000 ng/ml DON, which corresponds to in vivo exposure levels (about 0.1–1.0 mg DON/kg food/feed), which is assumed to be realistic within the average contamination level in both food and feed. According to our previous investigation, although the DON contamination levels in total adlay were 0.37–2.55 mg/kg, the bran levels were around 0.4–1.0 mg/kg adlay ( 5 ). Although high levels of trichothecene mycotoxins such as nivalenol and DON (>2,000 ng/ml) significantly influence enterocyte viability through activation of pro-apoptotic processes, ingestion of the realistic milder levels of DON (<1,000 ng/ml) retarded the epithelial cell migration (restitution), representing the initial step in the wound healing process in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 91%
“…Naturally occurring mycotoxins limit the utilization of medicinal materials and introduce potential risks to human and animal health. Fusarium head blight and its toxic metabolites such trichothecenes are present in adlay (family: Poaceae) as a rich source of Fusarium species ( 4 , 5 ). The trichothecene mycotoxins, a group of secondary metabolites produced by sesquiterpenoid fungi, are widely found with high prevalence in cereals, grains, feedstuffs, and indoor air ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure-based sampling and mycotoxin measurement would provide critical control points for the preventive reduction of fungal growth and mycotoxin production in the agricultural commodities. A recent study on the mycotoxin reduction in the medicinal plant adlay (Job’s Tears) demonstrated that the critical control point-based assessment was efficient to reduce the fungal growth and trichothecene production in the final product of the herbal medicine [ 30 ]. In addition to the diversities in the exogenous compounding factors affecting mycotoxin production in the medical herbs and spices, the quantitation methods should be the internationally recognized official methods of analysis, such as those by AOAC international.…”
Section: The Global Occurrence Of Mycotoxins In Medicinal Herbs Anmentioning
confidence: 99%